MODERN INNOVATIVE METHODS AND PEDAGOGICAL TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Dilmanov, Ilya (Журнал иностранных языков и лингвистики, 2025)
Currently, Uzbekistan is developing a new education system that is focused on entering the global educational space. This process is accompanied by significant changes in the pedagogical theory and practice of the educational process.